Desafios da saúde do trabalhador na atenção básica em Santos - Nemetz, Rosemeiry de Lima [UNIFESP] (2020)
Introduction: The population requires comprehensive assistance through an integrated and articulated SUS service network. In this context, Occupational Health has significant relevance due to the high rates of occurrence of work-related illnesses / accidents, including the attention of individuals in work situations, guaranteed by Law 8080/90. In the structure of the Brazilian health system, Primary Health Care is one of the main doors of entry for SUS and experiences the reality of work / health - disease processes in the territory and meets its underlying demands. Objective: Understand the meaning of work and its determination in the health-disease process in the territory, by the members of the Primary Care team and CEREST, and identify the difficulties and possibilities in the development of worker's health actions, with emphasis on integration and articulation. Method: Research with a qualitative approach through the use of thematic workshops resource with the professionals of CEREST Santos and the health units of Primary Health Care in the Northwest Zone and the Intermediate Waterfront, selected with a greater representation of residents notified in diseases related to the between 2013 and 2018. There were two groups, with a total of 14 professionals, 8 of which were Primary Care and 6 from CEREST, from June to November / 2019. The first two meetings of the workshops of each group took place at the Basic Health Unit of the selected territory and the last at CEREST- Santos, each meeting lasting two hours and a total of three meetings per group. The first two meetings of the workshops of each group took place at the Basic Health Unit of the selected territory and the last at CEREST Santos, with each meeting lasting two hours and a total of three meetings per group. The speeches collected in the workshops were analyzed using the Collective Subject Discourse method, in view of the need to know the subjectivities of individuals in relation to work relationships, through social representations. Results: The data collected showed similarities in both groups. Health professionals recognize that work is a determining factor in health, and is related to financial need, dignity and social identification. However, the lack of interaction with CEREST, as a point of technical support, through permanent health education makes it difficult to understand the reality of users 'work and the proposition of actions in the field of workers' health. Participants in Primary Care point out the need to raise awareness to expand the view of the care provided to the user-worker, in order to have an impact on the reception and changes in health practices, with a view to the principles of universality and comprehensiveness. They highlight the need for strategic planning, to trigger network work in order to guarantee access and resolution of services to users-workers, and health professionals themselves in overcoming their limits, through knowledge sharing and support.